Maternal Cystatin C Serum is Higher in Women with Severe Preeclampsia - Isasari, Kurnia M. (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the comparison between maternal cystatin C serum in severe preeclampsia and normal pregnancy. Method: This was an observational study with cross sectional analytic approach. The subjects are sixty women with severe preeclampsia and normal pregnancy who met inclusion criteria. The maternal serum level of cystatin C was automatically measured with Particle Enhanced Nephelometric Assay (PENIA). Result: Mean serum level of cystatin C in severe preeclampsia was 1.169 Â± 0.311 mg/l. Mean serum level of cystatin C in normal pregnancy was 0.929 Â± 0.166. There was a significant differences between maternal serum levels of cystatin C in women with severe preeclampsia compared with women with normal pregnancy. Conclusion: There was a significant differences between maternal serum levels of cystatin C in severe preeclampsia compared with normal pregnancy. [Indones J Obstet Gynecol 2014; 2-1: 22-27] Keywords: cystatin C, endotheliosis glomerulus, severe preeclamp